The Impact of E-Commerce Adoption Factors on the Growth of MSMEs E-Commerce Sales in Jabodetabek Area, Indonesia - Tirtana, Merryandi Queen; Hasudungan, Albert; Tjong, Valrhona Castella; Lukas, Erica Novianti (Journal of Entrepreneurship, Business and Economics, 2022)
The world is shifting digitally and just like humans, businesses need to adapt as well in order to keep up in this digital business era. In order to survive the current era, especially with the ongoing global pandemic, many micro, small, and medium enterprises (MSMEs) adopt e-commerce technologies to assist in their business growth. Several theories of e-commerce adoption have been proposed; the Technological Organizational and Environmental (TOE) Framework presents the impact of theoretical aspects in technology adoption. Therefore, this study aims to examine and identify how the TOE framework of e-commerce adoption contributes to improving the growth sales of MSMEs in the digital business era. The study utilizes cross-sectional data targeting 150 MSME owners and managers in Java’s Big City Clusters of Jabodetabek (Jakarta, Bogor, Depok, Tangerang, Bekasi). The analysis was divided into three stages of analysis: the multi-stage regression analysis, the confirmatory factor analysis, and the regression analysis. The final result shows that technological and organizational factors have a significant and positive relationship with the growth of MSME e-commerce sales. Meanwhile, the environmental factor shows otherwise due to external parties giving uncertainty to the growth of the business by adopting the technology. The negative result is affected by several factors, one of which is the use of latent variables, making it uncertain to sum any conclusion. Hence, it is implied that MSMEs need to continue or even improve business performance by being compatible with its infrastructure, and must be able to leverage the relative advantages of using the electronic commerce platforms as a tool. Moreover, MSMEs are expected to be ready to develop their business internally while remaining vigilant and prepared for future situations that may arise. Furthermore, policymakers should implement policies to support MSMEs in becoming multichannel sellers. Research paper Keywords: MSMEs; E-commerce; E-commerce Adoption Factors; TOE Framework; Jabodetabek Reference to this paper should be made as follows: Tirtana, M. Q., Hasudungan, A., Tjong, V. C., & Lukas, E. N. (2022). The Impact of E-Commerce Adoption Factors on the Growth of MSMEs E-Commerce Sales in Jabodetabek Area, Indonesia. Journal of Entrepreneurship, Business and Economics , 10 (2), 172–191.